Side group ratio as a novel means to tune the hydrolytic degradation of thiolated and disulfide cross-linked polyaspartamides. (June 2021) - Gyarmati, Benjámin; Mammadova, Aysel; Barczikai, Dóra; Stankovits, Gergely; Misra, Anil; Alavijeh, Mohammad S.; Varga, Zoltán; László, Krisztina; Szilágyi, András
Highlights: The hydrolytic stability of thiolated cationic polyaspartamides is controlled by side group ratio. Linear thiolated and disulfide cross-linked cationic polyaspartamides are mainly degraded by main-chain fragmentation. Rearrangement of intermolecular disulfide bridges results in disintegration of polyaspartamide hydrogels. Hydrolytic stability, swelling and haemocompability of polyaspartamides can be adjusted by side groups. Abstract: We describe the controlled degradation of cysteamine-modified polyaspartamides bearing N, N -dimethyl-2-aminoethyl (DME), N, N -dimethyl-3-aminopropyl (DMP) or 2-hydroxyethyl (HE) side groups. The hydrolytic stability of polyaspartamides was studied at pH = 7.7 and at pH = 5.5 to model extracellular and endosomal conditions, respectively. All derivatives were stable at pH = 5.5 whereas the presence of DME side groups induces degradation depending on the ratio of DME in polymer composition at pH = 7.7. The rate of degradation could be adjusted by varying the DME, DMP and HE content of polyaspartamides. Results of mass loss tests upon dialysis and molar mass change detected by size exclusion chromatography suggest that primarily main-chain degradation occurs in the presence of DME groups. Disulfide cross-linked hydrogels formed upon oxidation of thiol groups in polyaspartamides and the stability of the hydrogels could also be controlled by their composition. The analysis of water-soluble degradation products by NMR showed that dissolution of the hydrogels cannot be explained only by main-chain degradation, but the rearrangement of disulfide linkages also play a role by the decrease of the concentration of effective cross-linking points. The composition- and pH-dependent degradation of these polyaspartamides may find applications in biomedical fields that is supported by their low membrane disruption ability on red blood cells. Graphical abstract: Image, graphical abstract